When UAVs coexist with manned airplanes: Large‐scale aerial network management using ADS‐B. Issue 10 (12th August 2019) - Pan, Yan; Li, Shining; Li, Bingqi; Bhargav, B.; Ning, Zeyu; Han, Qingye; Zhu, Ting
Abstract: Increasing attention has been paid to employing the Automatic Dependent Surveillance‐Broadcast (ADS‐B) technology on unmanned area vehicles (UAVs). The critical challenge therefore emerges, ie, how to effectively schedule the UAVs without interfering the communication. An UAV management framework named uFly is proposed to address this challenge by controlling the total ADS‐B communication traffic over the air. The ADS‐B's interference probability is first modeled. Based on this model, the UAVs' ADS‐B traffic (as well as the number of flying UAVs) should match the manned airplanes' signals. By taking the manned airplanes' signals as the first‐class constraint, uFly then dynamically approves or denies UAVs for flight based on the real‐time number of airplanes. Finally, experiments using different data sets are conducted to verify the superior performance of uFly . Abstract : When employing the ADS‐B on UAVs for aerial network management, one critical challenge is to avoid interfere with the ADS‐B communication of airplanes. This paper presents a comprehensive framework namely uFly to manage UAV flights without causeing interference.